Intestinal carriage of invasive non-typhoidal Salmonella among household members of children with Salmonella bloodstream infection, Kisangani, DR Congo - Falay, Dadi; Hardy, Liselotte; Bonebe, Edmonde; Mattheus, Wesley; Ngbonda, Dauly; Lunguya, Octavie; Jacobs, Jan (Frontiers in Microbiology, 2023)
Introduction: Invasive non-typhoidal Salmonella (iNTS), mainly Salmonella Typhimurium and Salmonella Enteritidis) cause a severe burden in sub-Saharan Africa; however, its reservoir (animal or environmental) is unclear. The present study assessed healthy household members of index patients for intestinal carriage of Salmonella. Methods: Index patients were admitted to the University Hospital of Kisangani (DR Congo), and Salmonella grown from blood cultures. Household members were asked to provide three stool samples for culture for Salmonella. S. Typhimurium and S. Enteritidis isolates from index patients and household members were assessed for genetic relatedness using multiple-locus variable-number of tandem repeats analysis (MLVA), and the multilocus sequence type (ST) was determined by whole genome sequencing. Results: Between May 2016 and January 2020, 22 households were visited. The index patient serotypes were Typhimurium, Enteritidis, Typhi, and Paratyphi C; II:42:r:-; and I: 7 y:- (n = 8, 7, 5, and each 1, respectively). The median (range) delay between the index patient and household sampling was 25 days (2 days – 7.3 months); 203 household members provided at least one stool sample. Fifteen (7.3%) Salmonella carriers were found in 9/22 households. For one index patient, the household comprised S. Typhimurium in four household members, including the index patient, sampled 27 days after bloodstream infection; the MLVA types of these five isolates were similar. They belonged to ST313 Lineage 2 and were closely related ((0-1 Allelic Distance (AD) among the stool isolates and 8 AD with the blood culture isolate). In another household, the stool culture of the index patient (obtained 67 days after bloodstream infection) grew S. Enteritidis of the same MLVA type; both isolates belonged to ST11 Central/Eastern African clade and were closely related (3 AD). Discussion: The present study provides evidence of household clustering of S. Typhimurium ST313 and intestinal carriage of iNTS several weeks after bloodstream infection. Keys words: Invasive non-typhoidal Salmonella, Salmonella carriage, sub-Saharan Africa, Salmonella bloodstream infection, sub-Saharan Africa